2012
DOI: 10.1002/gps.3769
|View full text |Cite
|
Sign up to set email alerts
|

The association of psychotropic medication use with the cognitive, functional, and neuropsychiatric trajectory of Alzheimer's disease

Abstract: Objective The use of psychotropic medications in Alzheimer’s disease (AD) has been associated with both deleterious and potentially beneficial outcomes. We examined the longitudinal association of psychotropic medication use with cognitive, functional, and neuropsychiatric symptom (NPS) trajectories among community-ascertained incident AD cases from the Cache County Dementia Progression Study. Methods A total of 230 participants were followed for a mean of 3.7 years. Persistency index (PI) was calculated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
2
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 45 publications
(35 reference statements)
6
82
2
2
Order By: Relevance
“…Estes nossos resultados não corroboram com os estudos de Bourgeois e colaboradores (2015) que, ao explorar o impacto do consumo crónico das BZD´s sobre o declínio cognitivo de uma amostra de idosos institucionalizados constataram que, embora o funcionamento cognitivo dos sujeitos medido através do MMSE se deteriore ao longo do tempo, essa diferença não foi estatisticamente signi cativa entre os sujeitos que consomem BZD´s em relação aos que não consomem. Ainda assim, está bem patente na literatura que o uso prolongado de BZD´s constitui num fator de risco no aumento do declínio cognitivo em pessoas idosas (Bierman et al 2007;Moura, 2014;Paterniti, Dufouil & Alpérovitch, 2002;Zhang et al 2016) e, consequentemente, num aumento da incidência do desenvolvimento de perturbações neurocognitivas como a demência (Gage et al 2012;Gallacher, et al 2012), principalmente a Demência de Alzheimer (Rosenberg et al 2012). Paralelamente não foram encontradas diferenças signi cas entre o consumo de BZD´s e a sintomatologia depressiva medida pela GDS-15 (r pb = .118 , p<.528) e a sintomatologia ansiógena mediante os resultados obtidos GAI-SF(r pb = .130 , p<.486).…”
Section: Resultsunclassified
“…Estes nossos resultados não corroboram com os estudos de Bourgeois e colaboradores (2015) que, ao explorar o impacto do consumo crónico das BZD´s sobre o declínio cognitivo de uma amostra de idosos institucionalizados constataram que, embora o funcionamento cognitivo dos sujeitos medido através do MMSE se deteriore ao longo do tempo, essa diferença não foi estatisticamente signi cativa entre os sujeitos que consomem BZD´s em relação aos que não consomem. Ainda assim, está bem patente na literatura que o uso prolongado de BZD´s constitui num fator de risco no aumento do declínio cognitivo em pessoas idosas (Bierman et al 2007;Moura, 2014;Paterniti, Dufouil & Alpérovitch, 2002;Zhang et al 2016) e, consequentemente, num aumento da incidência do desenvolvimento de perturbações neurocognitivas como a demência (Gage et al 2012;Gallacher, et al 2012), principalmente a Demência de Alzheimer (Rosenberg et al 2012). Paralelamente não foram encontradas diferenças signi cas entre o consumo de BZD´s e a sintomatologia depressiva medida pela GDS-15 (r pb = .118 , p<.528) e a sintomatologia ansiógena mediante os resultados obtidos GAI-SF(r pb = .130 , p<.486).…”
Section: Resultsunclassified
“…Antipsychotic drugs were generally considered first-line drug treatment for various behavioral and BPSD, but serious adverse events, including an increased risk of stroke and mortality, limit their use (Mittal et al, 2011). For the treatment of sleep disturbances, BZDs and sedative antidepressants are utilized, but both of these drugs are associated with an increased risk of falls (Cumming and Le Couteur, 2003;Hartikainen et al, 2007;Coupland et al, 2011) and even cognitive decline (Barker et al, 2004;Rosenberg et al, 2012) among older individuals. A recent Cochrane review on pharmacotherapies for sleep disturbances in AD found no randomized-controlled trials on BZDR use among individuals with AD (McCleery et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, for the patients whose anxiolytic dose was increased, ADL functioning was impaired. In an earlier study, both antipsychotics and benzodiazepines were associated with a more rapid cognitive and functional decline in AD without an improvement in NPI [26]. Moreover, the use of antipsychotics and sedatives (including benzodiazepines) in 224 community-dwelling persons with AD was associated with a more than twofold risk of functional deterioration [27].…”
Section: Discussionmentioning
confidence: 99%